2021
DOI: 10.21203/rs.3.rs-281639/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitigation Effects of Vitamin C and E Against Copper Toxicity in Broiler Chickens, With Reference to Biochemical, Genotoxicity and Pathological Studies

Abstract: Copper (Cu) is necessary for biological utility, nevertheless when existing in abundance; it can produce plentiful injurious impacts. This enquiry was carried out to explore the efficiency of individual or combined doses of vitamin C (Vit C) and vitamin E (Vit E) in ameliorating some biochemical, genotoxicity and pathological changes in the liver of copper sulphate (CuSO 4 )-intoxicated chickens. One hundred- one day old broiler chicks were haphazardly divided into 5groups of 20 chicks each. The broilers we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In our previous study, we reported alterations in the liver tissues in Cu-intoxicated chickens represented by hyperplastic and necrotic biliary epithelium with various degenerative and necrotic changes at the third week. Also, cholestasis, necrotic bile duct epithelia, in addition to lymphocytic portal aggregation and fibroblast proliferation, were encountered at the 6th week [15]. Chronic exposure also leads to hemolytic anemia and affects the central nervous system [14,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we reported alterations in the liver tissues in Cu-intoxicated chickens represented by hyperplastic and necrotic biliary epithelium with various degenerative and necrotic changes at the third week. Also, cholestasis, necrotic bile duct epithelia, in addition to lymphocytic portal aggregation and fibroblast proliferation, were encountered at the 6th week [15]. Chronic exposure also leads to hemolytic anemia and affects the central nervous system [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…Both vitamins can function synergistically to inhibit the adverse outcomes of copper toxicity [12]. In our previous study, it was reported that a combination of vitamin C and E can mitigate the histopathological and DNA changes in the liver of CuSO 4 -intoxicated birds [15]. The present study aimed to evaluate the efficacy of single and combined supplementation of vitamin C and vitamin E in mitigating oxidative stress, erythrogram, leukogram changes, and histopathological alterations in the kidney induced by copper sulfate (CuSO 4 ) toxicity in broiler chickens.…”
Section: Introductionmentioning
confidence: 99%
“…Growth processes of the top cell are well explained in the reference article. [32] Even though the two materials have a lattice mismatch of about 3-4%, the MOVPE growth process is directed to a very specific growth condition for the nucleation of the coherently strained InP QWs and does not contain dislocations as experimentally demonstrated. [23] So, this structure is feasible from a fabrication point of view.…”
Section: Gainp/gaas Dual Junction Solar Cell Structure With Type-a In...mentioning
confidence: 96%
“…τ T becomes insignificant in the QW region due to a very small thickness of the quantum layers and even smaller depletion regions. [32] Increasing the thermionic emission reduces the τ esc , and more carriers will be transported.…”
Section: Electric Field In Qw Regionmentioning
confidence: 99%
“…While excessive copper in diet is linked with several detrimental effects on poultry. Supplementation of Cu in excess amount reduced the feed intake, growth and feed conversion ratio in birds (Hashem et al 2021). Numerous studies have verified the harmful effects of copper on birds (Yigit et al 2012;Hefnawy and El-khaiat 2015;Huang et al 2021).…”
Section: Causes Of Copper Toxicitymentioning
confidence: 99%